Factors associated with physicians' assessment and management of child abuse and neglect: A mixed method study - İNANICI, MEHMET AKİF; HIDIROĞLU, SEYHAN; YILDIZ İNANICI, SİNEM (ELSEVIER SCI LTD, 2020)
Physicians are a professional group that is highly likely to encounter abused or at-risk children. The aim of this study is to investigate physicians' experiences with abuse cases, their evaluations of abuse risk factors, and their attitudes toward becoming more educated on the subject. One-hundred-sixty-four family physicians at family health centers and public health centers completed a questionnaire, and a group of residents at a university training and research hospital were interviewed in a semi-structured format. One-fifth of the participants had managed a child abuse case at least once. Nearly half of the participants reported acting alone in diagnosing and managing abuse cases. Sixty-eight percent of these physicians stated they would like to receive training on this subject. Gender and having children did not make a difference as to the abuse-management experience of these medical professionals. Female participants placed more importance on risk factors related to children with mental disabilities and alcohol and substance abuse in parents than their male counterparts. Difficulties in diagnosis, concerns about handling the abuse cases, the impact of culture, various risk factors, the importance of teamwork and a holistic approach, the need for practical training, and the importance of primary prevention were themes that emerged from this survey. This study provides inferences as to which of the physician competencies should be targeted in undergraduate medical education.
Keywords: Prevention; Child; Legal notification; Barriers; Medical education; CONSEQUENCES; MALTREATMENT; IDENTIFICATION; FACILITATORS; DISCIPLINE; EXPERIENCE; KNOWLEDGE; ATTITUDES; FAMILIES; BARRIERS